2017
DOI: 10.1016/j.susc.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of the bulk-like electronic structure of manganese phthalocyanine beyond the first monolayer on Bi2Te3

Abstract: The evolution of electronic structure of manganese phthalocyanine on Bi 2 Te 3 shows a transition to a bulk-like aspect abruptly after completion of the first layer. This allows the inference that, in the first layer, there is charge transfer and electronic hybridization involving the occupied Mn-derived d orbitals of the molecule into the conduction band of the substrate. The charge transfer coupling is seen using angle-resolved ultraviolet photoelectron spectroscopy by monitoring the evolution of work functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…The recently increasing research efforts devoted to transition metal phthalocyanines (TMPcs) and porphyrins (TMPors) derive from their unique optical, electronic, and magnetic properties. , Fundamental magnetic interactions of TMPcs were found on various types of substrates, which may support their application in molecular quantum devices. On the other hand, the electronic configuration of the central metal atom of some TMPcs is still not completely understood and has been intensely debated in recent years, in particular, at interfaces. An impressive example for their complex electronic structure is iron phthalocyanine (FePc).…”
Section: Introductionmentioning
confidence: 99%
“…The recently increasing research efforts devoted to transition metal phthalocyanines (TMPcs) and porphyrins (TMPors) derive from their unique optical, electronic, and magnetic properties. , Fundamental magnetic interactions of TMPcs were found on various types of substrates, which may support their application in molecular quantum devices. On the other hand, the electronic configuration of the central metal atom of some TMPcs is still not completely understood and has been intensely debated in recent years, in particular, at interfaces. An impressive example for their complex electronic structure is iron phthalocyanine (FePc).…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account that organic molecules are usually weakly bonded to the substrate, the use of magnetic organic molecules has possibility to solve this problem. Transition metal phthalocyanines (TMPc, TM = Mn, Fe, Co, Ni, and Cu) are typical magnetic organic molecules that show different spin phenomena depending on the center TM atom. , The effect of TMPc adsorption on TIs has been widely studied using scanning tunneling microscopy (STM) and scanning tunneling spectroscopy (STS) , but less studied with photoelectron spectroscopy (PES). …”
Section: Introductionmentioning
confidence: 99%
“…The degree of tunability of charge and spin interactions offered by metal–organic layers has already been demonstrated on metallic surfaces. , The few systematic studies on TIs suggest a similar tunability, driven by the choice of either the metal ion or the ligand . Surprisingly, despite the considerably larger distance from the surface, compared to bare impurities, interactions between the molecular metal ions and the TSS can still be strong enough to lead to doping levels comparable to those observed for bare impurities, , form hybrid interface states, and, more dramatically, suppress the TSS from the first quintuple layer (QL), as recently found for cobalt phthalocyanine (CoPc) on Bi 2 Se 3 . A follow-up study concluded that nonperturbative interactions can only be achieved with molecules with nonplanar coordination geometry, where the metal ion is protected by the ligand core from surface-induced perturbations.…”
mentioning
confidence: 99%